Rancang Bangun Secure Mobile IP PBX Berbasis Raspberry Pi Dalam Mendukung Komunikasi Kegiatan Luar Taruna Akademi Angkatan Udara - Muhammad Kharrel Dwiadamajati; Muhammad Fahrurozi; Edi Supartono; Bambang Gastomo (Akademi Angkatan Udara, 2021)
The Air Force Academy is a candradimuka crater for prospective soldiers who will laterproduce Air Force officers who are Tanggon, Responsive and Trengginas. In their activities they carry out learning and practicing activities both inside and outside the knighthood. Outdoor activities are carried out in a field full of challenges. Under any circumstances and under any conditions the activity must be carried out properly. Communication is one of the main keys to the success of a mission. In this study, a secure mobile IP PBX based on raspberry pi 4. This VoIP server replaces the conventional PABX and is used as a means of communication even though there is no internet signal. The device is designed as a standalone PABX field that is not dependent on a particular vendor. The user uses a softphone that is embedded in the smartphone. In addition, the security side remains the main factor in maintaining the content of the communication content. This device is equipped with TLS and ZRTP protocols to prevent MiTM attacks from occurring. In the end, this device is a communication bridge when AAU cadets are carrying out external activities.